2014
DOI: 10.1136/heartjnl-2014-306118.4
|View full text |Cite
|
Sign up to set email alerts
|

4 Improving Undergraduate and Postgraduate Medical Trainees Confidence and Competence in Electrocardiogram Interpretation: Abstract 4 Table 1

Abstract: Introduction The Electrocardiogram (ECG) is the most commonly used diagnostic test in modern medicine.1Competency in ECG interpretation is central to undergraduate and postgraduate clinical training and minimising potential adverse consequences on patient care. Several studies have demonstrated postgraduates interpret ECG’s sub-optimally.2,3 Our study compares the effectiveness of two cost neutral learning strategies to improve competence and confidence in this core clinical skill. Method A prospective rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Approximately 59% of the medical students were regarded as having low confidence levels, with a total mean confidence score of 22.3 (SD 7.95) out of 40 points. In a study carried out among postgraduate foundation year 1 and 3rd-year medical students [ 19 ], they reported that respondents in the focused teaching program (FTP) group exhibited a greater improvement in confidence than the respondents of self-directed learning (SDL). However, among the medical interns in Al Ahsa [ 20 ], participants demonstrated insufficient performance in ECG interpretation despite completing advanced cardiac life support courses.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 59% of the medical students were regarded as having low confidence levels, with a total mean confidence score of 22.3 (SD 7.95) out of 40 points. In a study carried out among postgraduate foundation year 1 and 3rd-year medical students [ 19 ], they reported that respondents in the focused teaching program (FTP) group exhibited a greater improvement in confidence than the respondents of self-directed learning (SDL). However, among the medical interns in Al Ahsa [ 20 ], participants demonstrated insufficient performance in ECG interpretation despite completing advanced cardiac life support courses.…”
Section: Discussionmentioning
confidence: 99%